Effects of treadmill training on myelin structure repair after spinal cord injury in adult mice - SU Hong; PAN Lu; ZHU Ying; ANG Yunhang; LIU Yuan (陆军军医大学学报, 2023)
Objective To investigate the effects of treadmill training on the repair of myelin structure of dorsal corticospinal tract (dCST) in mice with T10 spinal cord mild contusion. Methods Twelve adult C57/BL female mice were used to construct and verify the model of spinal cord mild contusion, and another 30 mice were randomly divided into 3 groups (n=10): sham group, spinal cord injury (SCI) group, and treadmill training group.The mice of SCI and treadmill training groups were given unilateral (left) spinal cord contusion, while the sham group was given laminectomy only.A 4-week training scheme was conducted for the treadmill training group 1 week after SCI surgery (parameters: 12 m/min, 30 min/session, 1 time/day, 5 d/week).The primary motor cortex (M1) of mice in each group was injected with biotinylated dextran amine (BDA) to trace dCST 2 weeks before sampling, followed by the collection of tissue samples when the 4-week training finished.Then the expression levels of platelet-derived growth factor receptor α(PDGFRα), Ki67 protein, oligodendrocyte transcription factor 2(Olig2), adenomatous polyposis coli protein (APC/CC1) and myelin basic protein (MBP) were detected by immunofluorescence assay.Transmission electron microscopy (TEM) was also used to observe the myelination in the left dCST area.Moreover, Basso Mouse Scale (BMS) was performed in each group to evaluate the motor function of left hindlimb before injury, 1 week after injury and 1, 2, and 4 weeks after training. Results Immunofluorescent labeling showed that the ratio of PDGFRα/Ki67 double positive cells to the total number of PDGFRα positive cells, the ratio of Olig2/APC/CC1 double positive cells to the total number of Olig2 positive cells, as well as the mean fluorescence intensity of MBP in the left dCST area of the SCI group were significantly lower than those of the sham group (P < 0.01), while these indexes were higher in the treadmill training group than in the SCI group (P < 0.01).TEM results indicated that the G-ratio of the left dCST area was elevated in the SCI group (P < 0.01), but was reduced greatly in the treadmill training group (P < 0.01).Finally, the BMS scores were improved in the treadmill group at each detection time point after injury, but there was no significant difference as compared with the SCI group (P>0.05). Conclusion Treadmill training can facilitate the proliferation and differentiation of oligodendrocytes precursor cells (OPCs), improve the maturation of oligodendrocytes (OLs) in the left dCST region, and increase the expression of myelin related proteins, thus promoting the repair of myelin structure after SCI in adult mice.